Is the Quebec provincial administrative database a valid source for research on chronic non‐cancer pain?†. (24th June 2015) - Lacasse, Anaïs; Ware, Mark A.; Dorais, Marc; Lanctôt, Hélène; Choinière, Manon
Abstract Purpose The objective of this study was to evaluate the validity of diagnostic codes recorded in the Régie de l'assurance maladie du Québec (RAMQ) administrative database for identifying patients suffering from various types of chronic non‐cancer pain. Methods The validity of published International Classification of Diseases, Ninth Revision, coding algorithms for identifying patients with particular chronic pain syndromes in the RAMQ database was tested using pain specialist‐established diagnostic data of 561 patients enrolled in the Quebec Pain Registry, which was used as the reference standard. Modified versions of these algorithms (i.e., adaptation of the number of healthcare encounters) were also tested. For each algorithm, sensitivity, specificity, positive/negative predictive values, and their respective 95% confidence intervals (95%CI) were calculated. Results In the RAMQ database, some previously published algorithms and modified versions of these algorithms were found to be valid for identifying patients suffering from chronic lumbar pain (sensitivity: 0.65, 95%CI: 0.59–0.71; specificity: 0.83, 95%CI: 0.79–0.87), chronic back pain (sensitivity: 0.70, 95%CI: 0.64–0.76; specificity: 0.73, 95%CI: 0.68–0.78), and chronic neck/back pain (sensitivity: 0.71, 95%CI: 0.65–0.76; specificity: 0.78, 95%CI: 0.72–0.82). Algorithms to identify patients with other types of chronic pain showed low sensitivity: complex regional pain syndrome (≤0.07), fibromyalgia (≤0.42), and neuropathic pain (≤0.39). Conclusions Our study provides evidence supporting the value of the RAMQ administrative database for conducting research on certain types of chronic pain disorders including back and neck pain. Users should, however, be cautious about the limitations of this database for studying other types of chronic pain syndromes such as complex regional pain syndrome, fibromyalgia, and neuropathic pain. Copyright © 2015 John Wiley & Sons, Ltd.